Maternal-fetal transmission of Trypanosoma cruzi, a health problem slightly studied in Mexico: case Chiapas - Guillermina Campos-Valdez; Luisa Miguel Canseco-Ávila; Fernando González-Noriega; Oscar Alfaro-Zebadua; Ismael Yadird Nava-Medecigo; Enedina Jiménez-Cardoso (Instituto Nacional de Salud Pública, 2016)
Objective. To determine the Trypanosoma cruzi infection prevalence in 1125 pregnant women and the transmission frequency to their children from Tapachula and Palenque, Chiapas. Materials and methods. We determined the prevalence by serology tests and the transmission frequency by polymerase chain reaction (PCR) and T. cruzi reactivity capacity after 12 months. Results. Total maternal infection prevalence were 23/1 125 (2.04%), 9/600 (1.5%) were from Tapachula and 14/525 (2.6%) from Palenque. The seropositive women were between 20 and 35 years old, 31.8% have Premature Rapture of Membrane and 9.1% have history of perinatal death. The total percentage of positive newborns by PCR was 9/23 (39.13%), out of those 2/9 (22.2%) are from Tapachula and 7/14 (50%) from Palenque. The Maternal Fetal transmission frequency was. 2/9 (22.2%) in Tapachula and 1/14 (7.14%) in Palenque, all positive infants were asynthomatic. Conclusion. The maternal-fetal transmission rate in Chiapas State is variable; the reason could be the maternal immunological status and T. cruzi strain.